Modernité, anachronisme et ambivalence des risques et catastrophes naturelles à travers l’approche géohistorique - Nancy Meschinet De Richemond (Éditions en environnement VertigO, 2016)
Historical data allows to raise the problem of natural hazard consideration in territorial management in an original way. The cultural and historical context of the production of old documents about natural disasters must be interpreted to clarify the qualitative evolutions of what is not yet called the vulnerability. Reduce the historical diversity of disaster victims aids procedures to a « compensation » may be educational but illustrates an « épistémisation » process (Chouquer, 2008) : aids procedures can easily be reduced to its financial side, as it is usually the most important today. But it was not the same during the XVIIIth century in France. The historical overwhelmingly implicit context, within which these aids are organized must be specified and constructed. The geohistorical approach of risk is not only interesting in itself to detect stereotypes and anachronisms, but also allows to re-question the contemporary practices of hazard management. To make allowance for the diversity of facts and representations allows then to wonder about the positive and creative side of hazard and disaster. This ambivalence of risk and disaster is often claimed by the victims as the creator of social cohesion through an empirical and global management. While wanting to restore a positive side of the vulnerabilities, the resilience notion may prevent the integration of this creative side by contributing to strengthen the modern framework thinking established on division and high specialization ?